Volumetric analyses of ablation dimensions in microwave ablation for colorectal liver metastases - Iwan Paolucci; Simeon J. S. Ruiter; Jacob Freedman; Daniel Candinas; Koert P. de Jong; Stefan Weber; Pascale Tinguely (International Journal of Hyperthermia)
Background In thermal ablation of malignant liver tumors, ablation dimensions remain poorly predictable. This study aimed to investigate factors influencing volumetric ablation dimensions in patients treated with stereotactic microwave ablation (SMWA) for colorectal liver metastases (CRLM).Methods Ablation volumes from CRLM ≤3 cm treated with SMWA within a prospective European multicentre trial were segmented. Correlations between applied ablation energies and resulting effective ablation volumes (EAV) and ablation volume irregularities (AVI) were investigated. A novel measure for AVI, including minimum enclosing and maximum inscribed ellipsoid ablation volumes, and a surrogate parameter for the expansion of ablation energy (EAV per applied energy), was introduced. Potential influences of tumor and patient-specific factors on EAV per applied energy and AVI were analyzed using multivariable mixed-effects models.Results A total of 116 ablations from 71 patients were included for analyses. Correlations of EAV or AVI and ablation energy were weak to moderate, with a maximum of 25% of the variability in EAV and 13% in AVI explained by the applied ablation energy. On multivariable analysis, ablation expansion (EAV per applied ablation energy) was influenced mainly by the tumor radius (B = −0.03, [CI –0.04, –0.007]). AVI was significantly larger with higher applied ablation energies (B = 0.002 [CI 0.0007, 0.002]]); liver steatosis, KRAS mutation, subcapsular location or proximity to major blood vessels had no influence.Conclusions This study confirmed that factors beyond the applied ablation energy might affect volumetric ablation dimensions, resulting in poor predictability. Further clinical trials including tissue sampling are needed to relate physical tissue properties to ablation expansion.